2020
DOI: 10.3389/fcell.2020.578528
|View full text |Cite
|
Sign up to set email alerts
|

Cone Photoreceptor Degeneration and Neuroinflammation in the Zebrafish Bardet-Biedl Syndrome 2 (bbs2) Mutant Does Not Lead to Retinal Regeneration

Abstract: Bardet-Biedl syndrome (BBS) is a heterogeneous and pleiotropic autosomal recessive disorder characterized by obesity, retinal degeneration, polydactyly, renal dysfunction, and mental retardation. BBS results from defects in primary and sensory cilia. Mutations in 21 genes have been linked to BBS and proteins encoded by 8 of these genes form a multiprotein complex termed the BBSome. Mutations in BBS2, a component of the BBSome, result in BBS as well as non-syndromic retinal degeneration in humans and rod degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Their observations led to the hypothesis that PR OSs act as a "sink for membrane proteins", whereby the high membrane content of OSs makes them a default destination for membrane proteins, with the BBSome responsible for removing those proteins that should not reside in the OSs (reviewed by Seo & Datta 39 ). In support of this hypothesis, accumulation of the IS protein syntaxin3 in the OS of Bbs8 -/mice and bbs2 -/zebrafish was recently described 40,41 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Their observations led to the hypothesis that PR OSs act as a "sink for membrane proteins", whereby the high membrane content of OSs makes them a default destination for membrane proteins, with the BBSome responsible for removing those proteins that should not reside in the OSs (reviewed by Seo & Datta 39 ). In support of this hypothesis, accumulation of the IS protein syntaxin3 in the OS of Bbs8 -/mice and bbs2 -/zebrafish was recently described 40,41 .…”
Section: Discussionmentioning
confidence: 67%
“…To further investigate the role of the BBSome in photoreceptor function, we turned to the zebrafish, an established animal model for ciliopathies [42][43][44] . The cone-rich retina of zebrafish larvae represents a particular asset to study this photoreceptor subtype compared to the rod-dominated mouse retina, as diverging effects on cone and rod photoreceptors have been described 38,41,45 . In this work, we generated a new zebrafish bbs1 knock-out model and found that despite normal retinal development and photoreceptor differentiation, visual functional deficits were present prior to the appearance of any morphological anomaly in mutant fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very few studies have examined the activation or proliferative changes occurring in genetic degenerative models of similar human diseases. In one zebrafish study modelling Bardet-Biedl syndrome (BBS), a condition resulting in retinal degeneration due to defects in the photoreceptor outer segments, it was shown that little regenerative response was initiated from Müller cells following cone photoreceptor loss, despite displaying inflammatory responses [ 139 ]. Furthermore, high-intensity light damage could stimulate Müller glia-mediated photoreceptor regeneration in these mutants but only to pre-light injury levels [ 139 ].…”
Section: The Cmz and Its Potential To Prevent Retinal Diseasementioning
confidence: 99%
“…In one zebrafish study modelling Bardet-Biedl syndrome (BBS), a condition resulting in retinal degeneration due to defects in the photoreceptor outer segments, it was shown that little regenerative response was initiated from Müller cells following cone photoreceptor loss, despite displaying inflammatory responses [ 139 ]. Furthermore, high-intensity light damage could stimulate Müller glia-mediated photoreceptor regeneration in these mutants but only to pre-light injury levels [ 139 ]. A different study, using a cone and rod degenerative model, showed that Müller glial cells exhibited reactive gliosis before eventually transitioning into a regenerative state a few weeks following photoreceptor cell death due to activation by TNFα signalling [ 140 ].…”
Section: The Cmz and Its Potential To Prevent Retinal Diseasementioning
confidence: 99%